Medical tourists’ emotional and cognitive response to credibility and Servicescape - Loureiro, S. M. C. (Current Issues in Tourism, 2017)
While medical tourism has been an issue of increasing interest among scholars and practitioners, most studies are dedicated to understanding the factors of attraction that lead medical tourists to select a certain destination and treatment providers. In this vein, more studies are needed to understand medical tourists’ perceptions about medical facilities and staff, and repurchase intention formation. In order to contribute to bridging this gap, the current study aims to explore the effect of Servicescape (intrinsic cues) and credibility (extrinsic cues) on medical tourists’ emotion, perceived quality and image. The proposed model was tested in the medical tourism context in Portugal. The questionnaire was distributed to individuals who had stayed in a hospital devoted to medical tourism. A convenience sample of 332 usable questionnaires was employed to test the model. Findings reveal that ambience and design are the most important factors in formatting Servicescape itself. Servicescape and credibility are effective antecedents of customer image and pleasure-feeling. Credibility is more effective in enhancing pleasure-feeling and Servicescape in creating a favourable image. On the other hand, perceptions of quality do not contribute significantly to pleasure-feeling. Finally, the article also provides managerial implications and suggests avenues for further research.